EGF receptor signalling protects smooth-cuticle cells from apoptosis during Drosophila ventral epidermis development. - Urban, S; Brown, G; Freeman, M (2004)
Patterning of the Drosophila ventral epidermis is a tractable model for understanding the role of signalling pathways in development. Interplay between Wingless and EGFR signalling determines the segmentally repeated pattern of alternating denticle belts and smooth cuticle: spitz group genes, which encode factors that stimulate EGFR signalling, induce the denticle fate, while Wingless signalling antagonizes the effect of EGFR signalling, allowing cells to adopt the smooth-cuticle fate. Medial fusion of denticle belts is also a hallmark of spitz group genes, yet its underlying cause is unknown. We have studied this phenotype and discovered a new function for EGFR signalling in epidermal patterning. Smooth-cuticle cells, which are receiving Wingless signalling, are nevertheless dependent on EGFR signalling for survival. Reducing EGFR signalling results in apoptosis of smooth-cuticle cells between stages 12 and 14, bringing adjacent denticle regions together to result in denticle belt fusions by stage 15. Multiple factors stimulate EGFR signalling to promote smooth-cuticle cell survival: in addition to the spitz group genes, Rhomboid-3/roughoid, but not Rhomboid-2 or -4, and the neuregulin-like ligand Vein also function in survival signalling. Pointed mutants display the lowest frequency of fusions, suggesting that EGFR signalling may inhibit apoptosis primarily at the post-translational level. All ventral epidermal cells therefore require some level of EGFR signalling; high levels specify the denticle fate, while lower levels maintain smooth-cuticle cell survival. This strategy might guard against developmental errors, and may be conserved in mammalian epidermal patterning.